2020
DOI: 10.1002/eat.23294
|View full text |Cite
|
Sign up to set email alerts
|

How do you define recovery? A qualitative study of patients with eating disorders, their parents, and clinicians

Abstract: ObjectiveRecovery from an eating disorder (ED) may be defined differently by different stakeholders. We set out to understand the definition of ED recovery from the perspective of patients, their parents, and clinicians.MethodWe recruited patients with EDs (n = 24, ages 12–23 years) representing different diagnoses (anorexia nervosa n = 17, bulimia nervosa n = 4, binge‐ED n = 2, avoidant/restrictive food intake disorder n = 1), along with their parents (n = 20), dietitians (n = 11), therapists (n = 14), and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…De Young et al recently recommended that 6 months be used for recovery definitions of bulimia ( 17 ), whereas DSM-V classification provides unspecific guidance, i.e., « criteria not met for a sustained period of time » ( 1 ). Richmond et al reported four items for eating disorders recovery definition according to patients, parents and clinicians: (a) psychological well-being, (b) eating-related behaviors/attitudes, (c) physical markers, and (d) self-acceptance of body image ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Young et al recently recommended that 6 months be used for recovery definitions of bulimia ( 17 ), whereas DSM-V classification provides unspecific guidance, i.e., « criteria not met for a sustained period of time » ( 1 ). Richmond et al reported four items for eating disorders recovery definition according to patients, parents and clinicians: (a) psychological well-being, (b) eating-related behaviors/attitudes, (c) physical markers, and (d) self-acceptance of body image ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remaining with a lower BMI is common finding after total gastrectomy because of the lack of ghrelin signalling and of altered digestion steps. Her eating disorder has been undiagnosed during 15 (18). Mechanisms involved in this recovery are not totally understood but may be close to those involved in other situations of surgical resection of the stomach: (i) subtotal/ partial gastrectomy in bariatric surgery (gastric bypass, sleeve gastrectomy) and (ii) subtotal or total gastrectomy in surgical treatment of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Body image disturbance is a key symptom of anorexia nervosa (AN) and a significant predictor for poor treatment outcome, potentially through increasing stress and depression (Junne et al, 2019). Although patients assign a crucial role to body image for their recovery (Kenny, Boyle, & Lewis, 2019; Richmond et al, 2020), body image disturbance is still insufficiently understood, and hence the scarce specific therapeutic interventions are largely atheoretical or focus on targeting fear of weight gain (Ziser et al, 2018). The current study investigates whether a shifted weight bias, reflected in language use on body shapes and weight might contribute to the tenaciousness of body image disturbance in AN.…”
Section: Introductionmentioning
confidence: 99%
“…Three articles do not discuss behavior 20,33,37 because it is dominant in discussing nutrition. Most of the articles reviewed parenting, and only five pieces did not check it 20,23,29,34,38 . This parenting theme explains that children who experience ARFID can be associated with stressful parental conditions.…”
Section: Figure 1 Hierarchy Chart Using Nvivo 12 Plusmentioning
confidence: 99%
“…Furthermore, parental stress can be measured by the Parental Stress Index (PSI). Family themes were reviewed by 15 articles 21,[23][24][25][26][28][29][30][31][33][34][35][37][38][39] . The family's role is significant in facilitating a right environment for children and how families introduce the background to children early.…”
Section: Figure 1 Hierarchy Chart Using Nvivo 12 Plusmentioning
confidence: 99%